Analisis Tekanan Pori dan Karakteristik Overpressure pada Lapangan “GEO”, Cekungan Sumatra Selatan - Rizky Andra Prasetya; Budhi Setiawan (Universitas Negeri Gorontalo, 2026)
The presence of abnormal pore pressure zones in the South Sumatra Basin represents a significant technical challenge in drilling operations, with the potential to trigger serious incidents such as kicks and blowouts if not accurately predicted in advance. This study aims to estimate pore pressure values, characterize overpressure generation mechanisms, and identify their spatial distribution in the